AGE-DEPENDENT DECLINE IN ERYTHROCYTE ACETYLCHOLINESTERASE ACTIVITY: CORRELATION WITH OXIDATIVE STRESS - Jha, Rashmi; Rizvi, Syed Ibrahim (Biomedical papers, 2009)
Background: Oxidative stress hypothesis offers a mechanism for the aging process and its involvement in other pathologies such as diabetes and neurodegenerative diseases like Alzheimer. AChE activity in erythrocytes may be considered as a marker of central cholinergic status. The present study was undertaken to (i) determine the activity of erythrocyte AChE as a function of human process (ii) correlate AChE activity with oxidative stress during human aging.Material and Methods: Blood was collected from healthy subjects (n = 37) 22-82 years. Erythrocyte AChE activity, MDA and plasma antioxidant capacity in terms of FRAP was measured spectrophotometrically.Results: There was a marked decrease in AChE activity with increasing age. The reduction in activity of AChE correlated well with increased lipid peroxidation and a decrease in FRAP values.Conclusion: Decreased antioxidant defense, and alteration in membrane rheology during aging process both may contribute towards decreased activity of AChE in erythrocyte membrane. This finding may help in explaining the neuronal complications taking place under conditions of oxidative stress, aging, and dementia.
Keywords: Aging/Acetylcholinesterase/Oxidative stress/Erythrocyte/Membrane